Recent Immigrants Show improved Clinical Outcomes at a Tertiary Care HIV Clinic - Janet Raboud; Sandra Blitz; Tony Antoniou; Mona Loutfy; Sharon Walmsley (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In recent years, the proportion of patients attending tertiary care HIV clinics who are recent immigrants to Canada has increased dramatically.